The Controversial Long Term Effects of Parental Divorce: The Role of Early Attachment - Hazelton, Rosemary; Lancee, William; O'neil, Mary Kay (Journal of divorce & remarriage, 1998)
Using a multi-stage sampling methodology, 42 young adults from divorced families were compared with 42 matched subjects from intact families on measures of the quality of early parenting and the security of current attachment relationships. No long term effects of parental divorce were found. This was puzzling since a relationship was found between the quality of parenting and security of current attachment relationships. While subjects from divorced families were more likely to have rejecting parents, this vulnerability factor did not appear to affect security of current attachments. This apparent contradiction might be explained by the finding that contact with rejecting fathers was greatly reduced after separation. Conversely, subjects from intact families with rejecting fathers continued to be negatively affected.